An annotated bibliography on India written and/or published in the Philippines and are available in selected libraries in Metro Manila - Roy, Gautam (Institute of Library Science, University of the Philippines Diliman, 1988)
This bibliography is an empirical investigation of the materials on India written and/or published in the Philipines from 1947 to 1986 that are available in selected libraries in Metro Manila. It includes books, theses, dissertations, pamphlets, periodical and newspaper articles, conference papers, etc. gathered from fourteen state and private college/university libraries located in Metro Manila.